2014
DOI: 10.1007/s10856-014-5228-y
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and in vitro wound healing properties of novel clay based bionanocomposite films

Abstract: The present study investigates the development of methyl cellulose (MC)-sodium alginate (SA)-montmorillonite (MMT) clay based bionanocomposite films with interesting wound healing properties. The differential scanning calorimetry analysis of the composite films revealed presence of single glass transition temperature (Tg) confirming the miscible nature of the ternary blended films. The increase in MMT ratio in the composite films reduced the mobility of biopolymer chains (MC/SA) which increased the Tg of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 66 publications
(67 reference statements)
1
10
0
2
Order By: Relevance
“…Con- sequently, the observed decrease in the swelling ability of bionanocomposites, containing colloidal particles of Ag-Mt, can be considered as the superposition of two of these effects. Similar results were obtained in the work [17] when studying the kinetics of swelling of bionanocomposites of chitosan, Na-Mt and Ag-Mt and the kinetics of release of Ag + ions from these bionanocomposites. In the study of water uptake of films of chitosan and its composition with Na-Mt and Ag-Mt, it is found that chitosan composite comprising 10 % Na-Mt has the highest water absorption.…”
Section: Effect Of Ag + Ions On the Swelling Of Bionanocomposite Fsupporting
confidence: 88%
See 1 more Smart Citation
“…Con- sequently, the observed decrease in the swelling ability of bionanocomposites, containing colloidal particles of Ag-Mt, can be considered as the superposition of two of these effects. Similar results were obtained in the work [17] when studying the kinetics of swelling of bionanocomposites of chitosan, Na-Mt and Ag-Mt and the kinetics of release of Ag + ions from these bionanocomposites. In the study of water uptake of films of chitosan and its composition with Na-Mt and Ag-Mt, it is found that chitosan composite comprising 10 % Na-Mt has the highest water absorption.…”
Section: Effect Of Ag + Ions On the Swelling Of Bionanocomposite Fsupporting
confidence: 88%
“…Comparing these data with the kinetics of swelling of the considered BNCs in water (Fig. 4), it can be noted that the better the BNCs swells in water, the faster the Ag + ions are released from it, as found in [17].…”
Section: Kinetics Of Ag + Ions Release From Bionanocompositesmentioning
confidence: 72%
“…Results of scratch-induced wound healing assays reported by these authors demonstrated that clay mineral particles significantly delayed the gap closure in comparison with control experiments. For instance, while the control showed full gap closure within 24 h, palygorskite showed a mean gap closure of 59 ± 3% after 24 h. Polymeric composite films containing montmorillonite were evaluated by Salcedo et al [ 50 ] and Mishra et al [ 117 ]. The scratch assay showed, in both cases, that the presence of montmorillonite particles alone was able to alter cell behavior (Caco-2 and fibroblasts, respectively for each study), slowing down the gap closure.…”
Section: Resultsmentioning
confidence: 99%
“…It is likely that one of the reasons of microorganisms inactivation is the MMT can adsorb pathogenic bacteria, and this will provides a beneficial physical barrier against them (Mishra et al, 2014). It should be noted that dynamics of the microorganisms inactivation persists during a month.…”
Section: Antimicrobial Activity Of Filmsmentioning
confidence: 99%
“…Composites of natural biopolymers with aluminosilicates are used as packaging materials in the food industry (Tunç and Duman, 2011). Furthermore, clays are known to exhibit biological activity (Mishra et al, 2014); hence, biopolymers modified by bentonite can be used to design antimicrobial drugs and matrices for drug delivery. But biological activity of HOEC/bentonite composites is poorly understood, although it is important for medical applications.…”
Section: Introductionmentioning
confidence: 99%